NONVIOLENT COMMUNICATION AS A MEANS OF RESOLVING CONFLICTS IN THE STUDENT ENVIRONMENT (Psychology Travelogs, 2025)
The article examines nonviolent communication (NVC) as an effective and human-centered tool for preventing and resolving conflicts within the student community. The student environment is characterized by a high intensity of social interaction, diversity of personal values, varying levels of emotional maturity, and differences in communication strategies, which makes conflicts both inevitable and potentially transformative. Emphasis is placed on the need to strengthen constructive communication skills, as conflict situations often arise not from substantive contradictions but from emotional impulsivity, inaccurate interpretations, and insufficient differentiation between observations, feelings, and judgments.The article analyzes recent psychological and pedagogical research on communication culture, interpersonal interaction, and emotional competence, highlighting the contributions of Ukrainian scholars who view communication as a multi-component phenomenon that integrates communicative, perceptual, and interactive processes. Special attention is given to the scientific foundations of NVC developed by M. Rosenberg, whose model is based on empathy, awareness of needs, and respectful dialogue. The four key components of NVC—nonjudgmental observation, expression of feelings, identification of needs, and formulating requests instead of demands—are discussed as mechanisms that enhance mutual understanding and reduce defensive reactions.Empirical data on students’ communicative tolerance levels further demonstrate the relevance of implementing NVC practices in higher education institutions. The findings confirm that developing empathy, emotional regulation, and dialogical skills significantly contributes to minimizing interpersonal tensions and fostering a cooperative academic climate. Overall, the article substantiates the psychological role of NVC as a means of creating a culture of dialogue and supporting constructive conflict resolution among students.
Keywords: nonviolent communication; student conflicts; empathy; communicative tolerance; emotional competence; constructive dialogue